Extraction of lanthanides by polysulfone microcapsules containing EHPNA. I. Piercing method - 靖宇 王月 侯海龙 徐建鸿 王运东 (Journal of rare earths, 2015)
Since the conventional liquid-liquid extraction method suffered from a series of problems such as inefficiency of one stage extraction, vast device occupation and severe emulsification, we adopted microcapsule （MC） technique to change the former liq- uid-liquid extraction to liquid-solid extraction. Firstly, the piercing method was performed to prepare the empty polysulfone （PSF） microcapsules, which was easy to implement and control. Secondly, the ultrasonic approach was utilized to prepare the fimctional microcapsules containing 2-ethylhexylphosphonic acid mono-2-ethylhexyl ester （EHPNA）. We focused on a key factor of the molar ratio of PSF over 1-Methyl-2-pyrrolidinone （NMP）, attaining a loading ratio as high as 7.21 g-EHPNA/g-PSF. Thirdly, we examined the kinetics and thermodynamics of extraction. Kinetic results demonstrated that equilibrium was reached within two hours, with an extraction rate of Sm3＋=Er3＋〉La3＋ Thermodynamic results showed that the extraction of lanthanides complied wi~ the Langmuir law, with an extraction capacity of 0.25~2.30 mmol/g-microcapsule. Fourthly, stripping experiment indicated that three hours were re- quired to accomplish equilibrium for La3＋ and Sm3＋ while longer hours for Er3＋. Finally, seven extraction-stripping cyclic experiments were performed for three mixed elements, the results of which revealed that Sm3＋ and Er3＋ maintained constantly high extractiori amount whilst La3＋ leveled off at approximately 50%. This proposed polysulfone microcapsule containing EHPNA is suitable to be applied to extraction and concentration of rare earth metals.